Napper Tandy, The Irish Patriot. - (:unkn) unknown (Fores, S. W., 1798)
Scholarly notes may be added at a later date.
1 print : col.
Keywords: Caricatures; Cartoons; Tandy, James Napper, 1740-1803; United Irishmen